Formation and Function of a Collegiate Athletics Sustainability Committee - McCullough, Brian P.; Kellison, Timothy; Wendling, Elodie (Journal of Amateur Sport, 2018)
Institutions of higher learning may be considered dual-identity organizations because of the perceived distinctiveness between universities’ academic and athletic missions. One way in which these barriers can be weakened is through cross-sector social partnerships (CSSP), a form of collaborative engagement aimed at achieving a common societal goal. In this study, we examine the formation of a university-directed CSSP focused on enhancing environmentally sustainable initiatives within the athletic department. Interviews with 11 members of a so-called Green Team illustrate the processes of boundary spanning and boundary blurring. As demonstrated in the article, boundary spanning occurred under the leadership of a “champion” who assembled a team of stakeholders to assist with the major renovation of a pro-environmental football stadium. Though the sustainability committee has a common goal, not all experiences of Green Team members have been the same. In light of these differences, we identify key barriers and prescribe solutions that can lead to the realization of a new organizational form.